2014
DOI: 10.1088/1009-0630/16/10/11
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Thermoplastic Polyurethanes Laminated Glass Treated by Acid Etching Combined with Cold Plasma

Abstract: To overcome the problem of interlaminar delamination of thermoplastic polyurethane laminated glass, silicate glass was etched with hydrofluoric acid and thermoplastic polyurethane was then treated with cold plasma. Compared with the untreated samples, the interlaminar shear strength of acid etching samples, cold plasma-treated samples and acid etching combined with cold plasma-treated samples increased by 97%, 84% and 341%, respectively. Acid etching combined with cold plasma-treated samples exhibited a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The main cause of failure of laminated glass plates with PU interlayer is adhesion loss between glass and interlayer. However, recent findings identified that some treatments, such as the hydrofluoric acid etching of glass surface [10] or a cold plasma treatment on the PU [11], or a combination of both [12] may significantly increase the bonding strength, as well as the mechanical properties, without negatively affecting the transparency of laminated glass with PU.…”
Section: Introductionmentioning
confidence: 99%
“…The main cause of failure of laminated glass plates with PU interlayer is adhesion loss between glass and interlayer. However, recent findings identified that some treatments, such as the hydrofluoric acid etching of glass surface [10] or a cold plasma treatment on the PU [11], or a combination of both [12] may significantly increase the bonding strength, as well as the mechanical properties, without negatively affecting the transparency of laminated glass with PU.…”
Section: Introductionmentioning
confidence: 99%